The Influence of Evidence-Based Exercise and Age Reattribution on Physical Function in Hispanic Older Adults: Results From the ¡Caminemos! Randomized Controlled Trial. (March 2021) - Burrows, Brett; Andrade, Flavia Cristina Drumond; Piedra, Lissette; Xu, Shuo; Aguiñaga, Susan; Steinberg, Nessa; Sarkisian, Catherine; Hernandez, Rosalba
Older Hispanics routinely exhibit unhealthy beliefs about "normal" aging trajectories, particularly related to exercise and physical function. We evaluated the prospective effects of age reattribution on physical function in older Hispanics. Participants ( n = 565, ≥60 years) were randomly assigned into (a) treatment group—attribution-retraining, or (b) control group—health education. Each group separately engaged in four weekly 1-hr group discussions and 1-hr exercise classes, followed by monthly maintenance sessions. The Short Physical Performance Battery (SPPB) measured physical function throughout the 24-month intervention. No significant difference in physical function between intervention arms was evident over time. However, both groups experienced significant improvements in physical function at 24 months (β = 0.43, 95% confidence interval [CI] = [0.16, 0.70]). Participating in the exercise intervention was associated with improvements in physical function, although no additional gains were apparent for age attribution-retraining. Future research should consider strengthening or modifying intervention content for age reattribution or dosage received.